2000
DOI: 10.1093/jn/130.12.2932
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Supplementation Improves Cell-Mediated Immunity and Oxidative Stress of Asian Men and Women

Abstract: Vitamin E is an efficient antioxidant and a modulator of the immune system. Although racial differences in both baseline vitamin E level and immunologic subsets are known, no reliable data exist for the Asian population. Furthermore, the extent of the effect of alpha-tocopherol in protecting lymphocyte cells against oxidative stress and its association with cell-mediated immunity have not been elucidated. This study was undertaken to investigate the immunologic and antioxidant effects of vitamin E in healthy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 31 publications
7
74
2
Order By: Relevance
“…Taken together, these results show that vitamin E did not have any significant effect on immune modulation in healthy young subjects, unlike as reported in the Lee & Wan (21) study. The sample number used in the present study is similar, if not higher, than that used in the Lee & Wan (21) study.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Taken together, these results show that vitamin E did not have any significant effect on immune modulation in healthy young subjects, unlike as reported in the Lee & Wan (21) study. The sample number used in the present study is similar, if not higher, than that used in the Lee & Wan (21) study.…”
Section: Discussioncontrasting
confidence: 67%
“…The sample number used in the present study is similar, if not higher, than that used in the Lee & Wan (21) study. However, the lack of statistical significance could still be due to sample size, differences in the population or nutrition amongst the volunteers.…”
Section: Discussionmentioning
confidence: 90%
“…2, No. 6; and reducing the risk of cancer (Lee et al, 2000). However, -tocopherol is regarded as the most active and predominant form (Bender & Mayes, 2003).…”
Section: Tocochromanol Contents In the Rice Bran Cultivarsmentioning
confidence: 99%
“…Shimura et al [3] reported the depression of lymphocyte functions by lipid peroxidation induced by cumene hydroperoxide in rats' spleenocytes. Lee and Wan [4] reported that the short term supplementation of 233 mg of vitamin E to healthy subjects can modulate cell-mediated immunity and reduce oxidative stress.…”
Section: Introductionmentioning
confidence: 99%